2022
DOI: 10.3390/ijerph191710905
|View full text |Cite
|
Sign up to set email alerts
|

The Forms, Channels and Conditions of Regional Agricultural Carbon Emission Reduction Interaction: A Provincial Perspective in China

Abstract: Agricultural emission reduction is a key objective associated with sustainable agricultural development and a meaningful way to slow down global warming. Based on the comprehensive estimation of agricultural carbon emissions, this study applied the traditional spatial Durbin model (SDM) to analyze the type of regional emission reduction interaction and explore whether it is a direct or an indirect interaction caused by technology spillovers. Moreover, geographic, economic, and technical weights were used to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Moreover, the layout of the agricultural industry structure needs to be adjusted effectively. The degree of agglomeration of the agricultural industry is not enough to form a specific comparative advantage (He et al, 2022). Therefore, it needs to be expanded appropriately to form a professional market grid prospect by integrating planting, production, processing, and sales in a proper organizational structure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the layout of the agricultural industry structure needs to be adjusted effectively. The degree of agglomeration of the agricultural industry is not enough to form a specific comparative advantage (He et al, 2022). Therefore, it needs to be expanded appropriately to form a professional market grid prospect by integrating planting, production, processing, and sales in a proper organizational structure.…”
Section: Discussionmentioning
confidence: 99%
“…According to the sources of the agricultural carbon emissions, total agricultural carbon emissions (ACE) can be generally decomposed into 5 classifications [3,26]: (1) carbon emissions of the agricultural machinery, ACE AM ; (2) carbon emissions of the production and use of agricultural plastic film, ACE PF ; (3) carbon emissions of the production and use of pesticide, ACE PE ; (4) carbon emissions from irrigation, ACE IR ; and (5) carbon emissions of the production and use of fertilizers, ACE FE . Their simple mathematical relation is shown by Equation (1).…”
Section: Estimation Methods Of the Agricultural Carbon Emissions (Ace)mentioning
confidence: 99%
“…Yang et al [25] found significant positive spatial spillover effect in the carbon emissions, and therefore, they believed that local environmental governance is more important. He et al [26] also concentrated on the spatial spillover effect and found evidence that local governments with a low level of economic development tend to follow the carbon emission reduction policies provided by the highly developed surrounding regions. Guo et al [27] found that financial support will directly affect the agricultural carbon emissions and will also indirectly affect the agricultural carbon emission through the use of chemical fertilizer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The pathways for the low-carbon transformation of Chinese cities encompass the digital economy, industrial transformation and upgrading, and the spatial transfer of carbon emissions [22]. Furthermore, a comprehensive approach to straw utilization [12], investment in technological innovation [23], the enhancement of agricultural land-use types [24], economic and technological cooperation [25] and conservation tillage [26] can also make major contributions to reducing carbon emissions.…”
Section: Introductionmentioning
confidence: 99%